1994
DOI: 10.1080/07481189408252651
|View full text |Cite
|
Sign up to set email alerts
|

Defining the family after the death of a child

Abstract: We conducted 14 interviews representing 9 families and 10 child deaths to examine a d i h m a c o m m to bereaved parents-the dejnitian o f the family after the death of a child. Although the deceased child continued to be dejned as a member of the family to the par&, the degree to which this dejnition of the,family was presented to outsiders varied. The work of Boss (psychological presencelphysical absence and boundary ambiguity) and Goffman front-stage performancelbacbtage reality) jhcilitates an understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 10 publications
0
19
0
4
Order By: Relevance
“…The entire research process paralleled information found within the initial literature review, which indicated that the bereaved parents' grieving processes were individual journeys of redefining the self, as well as the family unit (Bernstein, Duncan, Gavin, Lindahl, & Ozonoff, 1989;Brabant, Forsyth, & McFarlain, 1994;Gudmundsdottir & Chesla, 2006;Martinson, Lee, & Kim, 2000;Rando, 1985;Reid, 2007;Riches & Dawson, 1996). The amount of support bereaved parents receive also affects their grieving processes.…”
Section: Introductionmentioning
confidence: 93%
“…The entire research process paralleled information found within the initial literature review, which indicated that the bereaved parents' grieving processes were individual journeys of redefining the self, as well as the family unit (Bernstein, Duncan, Gavin, Lindahl, & Ozonoff, 1989;Brabant, Forsyth, & McFarlain, 1994;Gudmundsdottir & Chesla, 2006;Martinson, Lee, & Kim, 2000;Rando, 1985;Reid, 2007;Riches & Dawson, 1996). The amount of support bereaved parents receive also affects their grieving processes.…”
Section: Introductionmentioning
confidence: 93%
“…Howarth (1998) has argued that the dead continue to exert an influence on the identity projects of the living, and this may be especially so in the case of surviving daughters. Brabant et al (1994) notes that some family Girls whose widowed fathers remarry 361 members hold on to their deceased loved ones as an abstract presence -a 'social ghost' -who still inhabits the family as they perceive it. Other family members may not.…”
Section: The Presence Of the Deceased In The Family Systemmentioning
confidence: 99%
“…Even my father, of all people, seemed to overlook the fact that there was a dead person about. Brabant et al (1994) show how family members differ dramatically in the degree of comfort they feel in portraying the family to outsiders following the death of a child. Similar dilemmas face daughters in families where the widowed father has remarried.…”
Section: Gordon Riches and Pam Dawsonmentioning
confidence: 99%
“…I tråd med funn fra den sparsomme forskningslitteraturen på området (Brabant et al, 1995;Dakof & Taylor, 1990;Thoits, 1995;Wertheimer, 1999) viste Omsorgsprosjektet at nettverksstøtten også, av ulike grunner, kunne vaere utilstrekkelig eller til og med skadelig, og således resultere i det motsatte av intensjonen (Dyregrov, 2003(Dyregrov, -2004. Det som etterlatte definerte som "ideell støtte" var identisk med støtte de hadde opplevd som "hjelpsom", mens "ikke hjelpsom støtte" representerte motsatsen til kontakt som var mest savnet eller belastende.…”
Section: Støtte Fra Sosiale Nettverkunclassified
“…ha med høyere forventninger mht. innhold og omfang av støtte til førstnevnte, og/eller at familiemedlemmer i mindre grad klarer å støtte de naermeste etterlatte fordi de selv er rammet av tapet (Brabant et al, 1995;Lehman et al, 1986). Mange av disse forventningene medførte skuffelser for de etterlatte (Dyregrov, 2003(Dyregrov, -2004.…”
Section: Mest Belastendeunclassified